PENGARUH HAMBATAN SAMPING TERHADAP KINERJA JALAN DI PERSIMPANGAN TIPE Y (Studi Kasus Simpang Pelor - Meulaboh) - Bambang Tripoli; Sofyan M. Saleh; Muhammad Isya (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2016)
Abstract:Meulaboh city has several intersections or junction one of them is Simpang Pelor Meulaboh which have 3 arms signalized between National Road, Iskandar Muda Street, and Teuku Umar Street. The problem statements in this research are how to determine side barriers, adequacy for parking space and the shape of corner at the outer side of the road, traffic volume and the level of service road. The purpose of the study are to estimate how complex side barriers, adequacy for parking space and the shape of corner parking, traffic volume and also the level of service to road performances. The method based on MKJI 1997. Based on the results weighted frequencies of occurrence the side barriers